2020
DOI: 10.1080/02786826.2020.1837340
|View full text |Cite
|
Sign up to set email alerts
|

Short-range bioaerosol deposition and recovery of viable viruses and bacteria on surfaces from a cough and implications for respiratory disease transmission

Abstract: Knowledge of respiratory bacterium/virus distribution on surfaces is critical for studying disease transmission via the contact route. Here, we investigated the bioaerosol deposition and distribution on a surface from a cough experimentally. A cough generator was used to release bacterium/virus-laden droplets. A solid surface was placed in front of the cough generator at different relative distances (D ¼ 0.2, 0.5, 0.8, and 1.1 m) and angles (h¼30 , 60 , and 90). Benign bacteria and bacteriophages were used sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…It was the same one used in our previous work. 28 The releasing velocity of cough droplets was around 12 m/s which is similar to the average cough droplet velocity of 11.7 m/s. The size distribution was similar to a real cough with the peak size of 10-20 µm.…”
Section: Experimental Setup and Studied Casessupporting
confidence: 63%
See 1 more Smart Citation
“…It was the same one used in our previous work. 28 The releasing velocity of cough droplets was around 12 m/s which is similar to the average cough droplet velocity of 11.7 m/s. The size distribution was similar to a real cough with the peak size of 10-20 µm.…”
Section: Experimental Setup and Studied Casessupporting
confidence: 63%
“…After the deposition and sample collection, one part of the sample with size of 1 cm × 5 cm or 1 cm × 11 cm was cut for inspection using a microscope (Ni‐E, Nikon, Japan) to obtain the number concentration of deposited droplets. A microscopy method similar to our previous work was employed 28 . The droplets on pictures were automatically identified and counted by the software of the microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Dudalski et al [ 36 ] measured the far-field human cough airflows from healthy and influenza-infected subjects, and obtained the time variation of peak velocity in the center of airflow jet but did not discuss the velocity distributions. Wang et al [ 37 ] measured the velocity using PIV and captured droplets on a solid surface that subjects faced when coughing. Although their frequency was very high (12,500 Hz), their research mainly focused on the distribution of droplets while not the airflow characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that Bourouiba et al [ 38 ] observed the trajectory of droplets from human sneezes with a very high-frequency PIV (up to 8000 Hz). Wang et al [ 35 ], and Wang et al [ 37 ] utilized a higher PIV (frequency >10,000) to measure the cough but did not explore the detailed velocity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…coli was used to represent the bacterial pathogens inside cough droplets, while some infectious diseases are transmitted via virus laden aerosols. The study from Wang, Fu, and Chao (2020) found that bacteria or viruses inside cough droplets did not affect the short-range bioaerosol deposition and distribution on the front surfaces. Thus, it was expected that the results of this work based on bacterium E.coli could represent both the bacterium and virus laden droplet deposition on front person.…”
Section: Discussionmentioning
confidence: 94%